2017
DOI: 10.1016/j.jacc.2017.03.557
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Factors and Incidence of Heart Failure Hospitalization in the Women’s Health Initiative

Abstract: BACKGROUND Reproductive factors reflective of endogenous sex hormone exposure might have an effect on cardiac remodeling and the development of heart failure (HF). OBJECTIVES This study examined the association between key reproductive factors and the incidence of HF. METHODS Women from a cohort of the Women’s Health Initiative were systematically evaluated for the incidence of HF hospitalization from study enrollment through 2014. Reproductive factors (number of live births, age at first pregnancy, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 40 publications
2
39
3
Order By: Relevance
“…Although our cohort has a reasonable size, the incidence of HF is still low because of the relatively young age of the participants, with a median of 52.9 (IQR 46.9-59.1) years. In the approximately equally sized Women's Health Initiative Study, the number of heart failure endpoints was twice as high as in our study, with an average baseline age of the participants of 62.7 (SD 7.1) years [16].…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Although our cohort has a reasonable size, the incidence of HF is still low because of the relatively young age of the participants, with a median of 52.9 (IQR 46.9-59.1) years. In the approximately equally sized Women's Health Initiative Study, the number of heart failure endpoints was twice as high as in our study, with an average baseline age of the participants of 62.7 (SD 7.1) years [16].…”
Section: Discussioncontrasting
confidence: 43%
“…Our results are in line with the recent findings of the Women's Health Initiative, where the age-adjusted estimate for AAM was 0.96 (95%CI 0.93-0.99), and the multivariateadjusted estimate was 0.98 (95% CI 0.95-1.00). 16 BMI may be the causal link, since genetic variants for earlier AAM and BMI have been reported to overlap [9], and BMI is itself an important risk factor for hypertension and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The increased prevalence of HFpEF in older women compared with men of the same age appears related to the loss ovarian hormones, and primarily estrogens, that occur during menopause (7,26). Epidemiologic evidence further suggests that premature or early natural menopause (27)(28)(29) and a shorter total reproductive duration positively associate with incident heart failure (30). Hall et al (30) showed that the incidence of HFpEF was higher in postmenopausal women who were nulliparous, further suggesting a role of endogenous estrogens in the pathogenesis of the disease process.…”
Section: What Evidence Supports a Role For Estrogen In The Maintenancmentioning
confidence: 99%
“…Epidemiologic evidence further suggests that premature or early natural menopause (27)(28)(29) and a shorter total reproductive duration positively associate with incident heart failure (30). Hall et al (30) showed that the incidence of HFpEF was higher in postmenopausal women who were nulliparous, further suggesting a role of endogenous estrogens in the pathogenesis of the disease process. Importantly, diastolic dysfunction, the harbinger of HFpEF, was recently described as part of the "postmenopausal syndrome" (31).…”
Section: What Evidence Supports a Role For Estrogen In The Maintenancmentioning
confidence: 99%
“…LVEF) among the original generation and the relatively young age of 62 generation three (baseline age < 40 years old), we only included the offspring generation in 63 the analysis. In total, we conducted the proposed analyses among 1,871 AA women in the 64 JHS, 1,764 EA women in the FHS, and 3,461 HA women in the WHI-SHARe.In the WHI, HF adjudication was based on the Atherosclerosis Risk in Communities 68 (ARIC) classification guidelines17 , in which HF was defined as having acute decompensated 69 HF (ADHF) and chronic stable HF18 . Participants with adjudicated HF were further classified 70as HFrEF or HFpEF according to their LVEF.…”
mentioning
confidence: 99%